Optimizing Gravity-Fed Sewer Systems using GRG and PGSL: A Path to Cost-Effective Design - Keawsriyong, Teerapat; Wipulanusart, Warit; Leelatanon, Satjapan; Suksuwan, Nukul; Weekaew, Jakkarin; Bao Pham, Quoc; Ditthakit, Pakorn (Engineering, Technology & Applied Science Research, 2025)
In this paper, Generalized Reduced Gradient (GRG) and Probabilistic Global Search Lausanne (PGSL) optimization algorithms are employed to enhance sewer network design, focusing on link length, path, diameter, and cost. The former are compared with linear and dynamic programming, with the results indicating PGSL as the most cost-efficient, achieving optimal lengths of 70.00 m for Link I, 48.97 m for Link II, and 76.41 m for Link III, with paths of 1-2, 1-2, and 1-3, respectively, and a total cost of $15,688.17. In comparison, other algorithms incurred higher costs, while the optimal diameters remained consistent across all methods, ensuring structural integrity. The minor variations in lengths and paths reflect network design robustness. The importance of selecting the right optimization algorithm based on cost, length, path, and diameter is emphasized. PGSL is introduced for the first time in this context, demonstrating superior cost-effectiveness and significant implications for sewer network optimization. The findings provide valuable insights to engineers and planners, promoting more efficient and sustainable infrastructure development.